2003
DOI: 10.1063/1.1560871
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric nematic suspension

Abstract: We report on the development of a dilute suspension of ferroelectric particles in a nematic liquid-crystal (LC) host. We found that the submicron particles do not disturb the LC alignment and the suspension macroscopically appears similar to a pure LC with no readily apparent evidence of dissolved particles. The suspension possesses enhanced dielectric anisotropy, and is sensitive to the sign of an applied electric field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
179
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(184 citation statements)
references
References 17 publications
3
179
1
1
Order By: Relevance
“…In our simple model, in the ferroelectric liquid crystal suspension, the dependence of the angular distortion on the electric field is similar to that in the pure system with effective dielectric function anisotropy given by voltage [6]. We shall present elsewhere a more complete general effective medium theory for ferroelectric liquid crystal suspension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our simple model, in the ferroelectric liquid crystal suspension, the dependence of the angular distortion on the electric field is similar to that in the pure system with effective dielectric function anisotropy given by voltage [6]. We shall present elsewhere a more complete general effective medium theory for ferroelectric liquid crystal suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Reznikov et al [6] report that their Sn colloidal particles possess a spontaneous polarization of 14 µC/cm …”
Section: Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…carbon nanotubes, silica microbeads, nanoparticles and various collides exhibit remarkable new physical phenomena. Experiments have shown that nanoparticles and ferroelectric nanoparticles can greatly enhance the physical properties of nematic and smectic liquid crystals [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%